Finite Element Method (FEM) simulation of static and dynamic compression test of materials - Ong, Dalton Ke Yuan (2017)
The Static compression test and the Split Hopkinson Pressure Bar test are the most commonly used method to determine the material properties of the specimen, in this case, Aluminum T6061. Some of the properties that is of interest includes the strain rate, deformation rate, stress strain experienced as well as the young modulus of specimen. This report seeks to use Finite Element Method (FEM) to investigate the relationship of stress strain properties in Aluminum T6061 by means of simulation software. This simulation software includes the use of Ansys workbench 17.1 and Ansys LSDYNA (explicit dynamics) to simulate real time static and dynamic compression of the specimen. Ansys workbench 17.1 is used to simulate static compression for AL T6061. The plastic model for this experiment is Johnson Cook Model and stress strain curve is generated for the calculation of Young Modulus. Specimen is also created with imperfect parallelism on purpose to investigate the effects of manufacture defects on simulation results. As for dynamic compression, Ansys workbench is used together with Ansys LSDYNA to produce more detailed charting results. The velocity of striker bar is varied between 10.5m/s, 13.3m/s and 15m/s to examine the different strain rates across the specimen and its degree of deformation over time.